2015
DOI: 10.1103/physrevb.91.104108
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the large piezoelectric activity in(1x)Ba(Zr0.2Ti

Abstract: The diffusionless pseudobinary phase diagram, monodomain properties, and free energy of (1 − x)Ba(Zr 0.2 Ti 0.8 )O 3 -x(Ba 0.7 Ca 0.3 )TiO 3 are computed for comparison with experimental results. Specifically, the variation of the spontaneous polarization, anisotropy energy, and free energy with respect to temperature, composition, and polarization direction are discussed relative to the results of resonant piezoelectric measurements performed over a wide compositional range as a function of temperature. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 62 publications
9
83
0
Order By: Relevance
“…Liu and Ren proposed that large the piezoelectric response for BZT-BCT is associated with the starting point of MPB, i.e., the C-T-R triple point, which shows a tricritical behavior with the crossover between first order and second order transition (as shown in Figure 12) [14]. On the other hand, it has also been proposed that there is no need for the coincidence between the tricritical point and the triple point, and Acosta et al pointed out that the maximum coefficient d 33 value (best piezoelectric property) does not occur at the triple point [74][75][76]. This indicates the irrelevance between the tricritical point and the high piezoelectric response.…”
Section: Tricritical Phenomenonmentioning
confidence: 99%
“…Liu and Ren proposed that large the piezoelectric response for BZT-BCT is associated with the starting point of MPB, i.e., the C-T-R triple point, which shows a tricritical behavior with the crossover between first order and second order transition (as shown in Figure 12) [14]. On the other hand, it has also been proposed that there is no need for the coincidence between the tricritical point and the triple point, and Acosta et al pointed out that the maximum coefficient d 33 value (best piezoelectric property) does not occur at the triple point [74][75][76]. This indicates the irrelevance between the tricritical point and the high piezoelectric response.…”
Section: Tricritical Phenomenonmentioning
confidence: 99%
“…[11,13,14,21] The overall pattern of softening and stiffening observed here both at 0. with BTO is revealing, however, in that, while there are some close similarities in the mechanical properties, there are also some important differences.…”
Section: Discussionmentioning
confidence: 51%
“…Precursor softening evident in Figure 4 for both BTO and BZT-50BCT is the same as has been reported previously for RUS data from BTO [30][31][32] and is attributed largely to the effect of dynamical polar nanoregions (PNRs). These acquire a static or quasi-static component that is most likely responsible for the anelastic loss seen as increasing tanδ and Q -1 from ~10-20 K above T c , and would account also for the small residual values of the piezoelectric coefficient in a 10 K interval above T c reported by Acosta et al [11] and in a 30 K interval above T c by Damjanovic et al [29] This effect can also be observed in the dielectric results of BZT-50BCT in Fig.3c.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations